Speculation fit for a king? Medical announcements from the British royal family and the recurring ethical complexities of personal privacy and public commentary from physicians - Alexander Smith; Dinesh Bhugra; Antonio Ventriglio; Michael Liebrenz (BMC Medical Ethics, 2024)
Abstract This article explores the ethical complexities of openly-expressed medical commentary using recent cancer diagnoses within the British monarchy as illustrative cases. Specifically, it examines tensions between public interest, personal privacy, and professional standards, underlining the adverse implications of conjectural discourse, alongside the role of physicians in enhancing wider medical understanding.